Potential disruption of thyroid hormones by perfluoroalkyl acids in an Arctic seabird during reproduction. (15th July 2022) - Choy, Emily S.; Elliott, Kyle H.; Esparza, Ilse; Patterson, Allison; Letcher, Robert J.; Fernie, Kim J.
Abstract: Arctic marine ecosystems are experiencing rapid change, such as ocean warming and enhanced pollutants. Perfluoroalkyl acids (PFAAs) arriving via long-range transport have been detected in Arctic wildlife, including seabirds which are considered sentinels of marine ecosystem health. There is evidence that PFAA exposure leads to the disruption of thyroid hormones (THs), such as thyroxine (T4) and triiodothyronine (T3), which play important roles in metabolism, incubation, and thermoregulation in seabirds. Here, we investigated relationships between PFAAs and THs [total T4 (TT4), free T4 (FT4), total T3 (TT3) and free T3 (FT3)] in blood plasma collected from 63 thick-billed murres ( Uria lomvia ) at a colony located in northern Hudson Bay (2016–2018). We then tested if PFAAs and TH levels were related to fitness-associated reproductive traits, such as body mass and hatch dates. PFUdA, PFOS, and PFTrDA were the dominant PFAAs in murre blood, accounting for approximately 77% of ∑PFAA. Females had higher PFAAs than males, possibly due to higher trophic feeding. While FT3 increased with PFOS, PFNA, PFDA, PFDoA, PFTeDA, ∑PFCA7, and ∑PFAA in murres, TT3 decreased with PFOS, PFDoA, and PFTeDA in males, but not females, suggesting thyroid disruption. TT3 increased with body mass, whereas several long-chain PFAAs were negatively correlated with body mass. Negative relationships between PFNA, PFDoA, PFTrDA, PFTeDA, and ∑PFAA with hatch dates may be the result of a disruption in incubation behaviour, resulting in earlier hatch dates. Consequently, TT3 concentrations were highest in males and females in 2018, a year in which PFAAs were lowest and hatch dates were delayed relative to 2017. As an Arctic seabird experiencing several indirect effects of climate change, the interaction of PFAAs on thyroid activity may cause additional stress to murres. Graphical abstract: Image 1 Highlights: Free triiodothyronine (T3) positively associated with PFOS and long-chain PFAAs. Total T3 decreased with PFOS and long-chain PFAAs in males, suggesting disruption. Higher trophic feeding may explain higher long chain PFAAs in females than males. Higher long-chain PFAAs associated with lower body mass. PFAAs associations with earlier hatch dates may be due to disruptions in incubation.